El enfoque del nacionalismo cultural en la cooperación bilateral en la lucha contra el tráfico ilícito de bienes culturales: el caso de Ecuador e Italia - Gonzales Sánchez, Andrea Paola (2020)
According to the United Nations Educational, Scientific, and Cultural Organization (UNESCO), the illicit trafficking of cultural property corresponds to activities of illegal trade of objects that have a historical, archaeological, anthropological, or artistic interest. This phenomenon is considered an international crime since the UNESCO 1970 Convention on the Means of Prohibiting and Preventing the Illicit Import, Export and Transfer of Ownership of Cultural Property. This treaty marks a worldwide starting point not only for the trafficking of heritage as an illegal activity but also for the promotion of the bases of solidarity and international cooperation in this field. In this context, Ecuador and Italy have carried out important cooperative work to promote the protection of cultural heritage and the international fight against illicit trafficking in cultural property based in a relationship of Complex Interdependence, which reflects their common conception of Cultural Nationalism, a perspective that emphasizes the priority of States over their own heritage and its in situ conservation. According to Keohane and Nye’s (1988) theory of Complex Interdependence through membership of international institutions (governmental and non-governmental organizations, international regimes and conventions), States can expand their own interests though the use of cooperation as an instrument. This research seek to understand the motivations for this bilateral cooperation, considering that the Governments of both countries have worked in coordination to adopt common measures against the cultural property illicit trafficking phenomenon: exchange of information and intelligence; establishment of institutional contacts to facilitate cooperation; legal and technical training activities aimed at preventing and combating illicit trafficking of cultural property; and, above all, the recovery of heritage objects exported illegally.